2020
DOI: 10.1002/jbt.22662
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of metformin against HT29 colon cancer cells contributes to mitochondrial Sirt3 upregulation

Abstract: Cancer and diabetes, the two mitochondria‐related diseases, have recently been linked to silent mating‐type information regulation 2 homolog 3 (SIRT3) activity irregularities. In this study, the effect of metformin, an antidiabetic with anticancer properties, has been evaluated on mitochondrial functionality markers, cell death pathways, and SIRT3 enzyme activity in the colon cancer cell line, HT‐29, and human embryonic kidney cells (HEK 293). HT‐29 cells were treated with metformin (5, 10, 20, 40, and 80 µM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
3
16
1
Order By: Relevance
“…This study revealed cell cycle arrest with increased p21 and p27 alongside decreased CCND1 and CCND3 genes and proteins following in vivo and in vitro treatment with VD 3 and metformin monotherapies, con rming many reports that proclaimed suppression of cell cycle by both agents [20,21,[24][25][26][27][28]. However, in vivo, and in vitro metformin single treatment also showed higher cell death, increased gene, and protein expression of apoptosis markers and PTEN, and downregulations of the PI3K/Akt/mTOR molecules, whereas the VD 3 monotherapy effects were weaker.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This study revealed cell cycle arrest with increased p21 and p27 alongside decreased CCND1 and CCND3 genes and proteins following in vivo and in vitro treatment with VD 3 and metformin monotherapies, con rming many reports that proclaimed suppression of cell cycle by both agents [20,21,[24][25][26][27][28]. However, in vivo, and in vitro metformin single treatment also showed higher cell death, increased gene, and protein expression of apoptosis markers and PTEN, and downregulations of the PI3K/Akt/mTOR molecules, whereas the VD 3 monotherapy effects were weaker.…”
Section: Discussionsupporting
confidence: 80%
“…A plausible explication for the disagreement between the present and the earlier in vivo and in vitro studies on the VD 3 anti-cancer e cacy could be related to the relatively shorter treatment durations ( 4weeks & 12h, respectively) in our study compared with longer timepoints (≥ 8 weeks & ≥ 24h, respectively) in the prior reports [21,32,53,54]. We also hypothesise that the superiority of metformin proapoptotic effects over VD 3 , with and without 5-FU, could involve better attenuations of the PI3K/Akt/mTOR oncogenic molecules by inducing the expression of the tumour suppressor protein, PTEN, thus promoting oxidative metabolism and subsequently mitochondrial-induced apoptosis in neoplastic cells [24][25][26][27][28]. Moreover, the triple therapy in the present study showed the best tumoricidal actions against CRC and could represent the best strategy for treating early and late stages of colon neoplasia.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The majority of cancer diseases, including CRC, are characterized by mitochondrial dysfunction and increased oxidative stress with mitochondrial dysfunction affecting a wide range of metabolic pathways [11][12][13]. Mitochondrial function and integrity are controlled by the mitochondria guardian SIRT3 which acts on numerous substrates to activate fat oxidation, amino acid metabolism and electron transport [14][15][16]. In SW620 CRC cells, SIRT3 silencing led to a decreased mitochondrial biogenesis, which in turn affected cell viability [17].…”
Section: Introductionmentioning
confidence: 99%